P88 | REGENERATIVE MEDICINE, REHABILITATION AND CYTO-HISTOCHEMISTRY: RECENT EVALUATIONS OF INTEGRATED TREATMENTS (European Journal of Histochemistry)
Regenerative medicine is a rapidly evolving field that focuses on repairing, replacing, or regenerating damaged tissues and organs. Recent advancements in this field have shown promising results in various areas, including tissue engineering and rehabilitation. The Italian Academy of Bio-Regenerative Medicine (BIORI) is a group of health Italian operators, about a hundred all over Italy, involved in developing all the new science regenerative technologies. We also are involved in using and promoting many less-invasive, surgical approaches or non-surgical regenerative orthopedics. The current experiences and guidelines, published on the best international papers, are currently applied in our daily work following the Italian rules and laws. What is interventional non-surgical regenerative orthopedics? It represents an innovative, natural, and highly successful alternative to common medical approaches to conditions that would otherwise require surgery. This exciting field opens opportunities to treat orthopedic or musculoskeletal injuries, arthritis, and other degenerative conditions by using a tissue preservation strategy that uses the body’s own healing cells to help restore more normal function to the human body. Regenerative orthopedic procedures encourage your body to heal and strengthen the damaged tissue. Advanced treatment protocols concentrate your own platelets, growth factors, and stem cells and deliver them precisely (under image guidance) into the site of your injury to support and promote natural healing. Applications in Rehabilitation involved: - nerve Regeneration: researchers are exploring the use of biomaterials and tissue engineering strategies to promote nerve regeneration. Studies have shown promising results in using nerve conduits and scaffolds to support nerve growth and repair. - muscle Regeneration: decellularized extracellular matrices (dECM) are being used to promote muscle regeneration. Researchers have shown that dECM can support muscle cell growth and differentiation, making it a promising tool for muscle tissue engineering. - bone Regeneration: biomaterials like hydroxyapatite and bioactive glasses are being used to create scaffolds for bone regeneration. These scaffolds can promote bone growth and osteointegration, making them suitable for orthopedic applications. In the field of tissue engineering cyto-histochemistry plays a crucial role in tissue engineering, allowing researchers to analyze tissue structure and cell behavior. This knowledge can be used to develop more effective tissue engineering strategies. Moreover, understanding cellular response to biomaterials and tissue engineering strategies is essential for developing effective regenerative medicine treatments. Researchers are using cyto-histochemistry to study cellular behavior and optimize treatment outcomes. Overall, regenerative medicine, rehabilitation, and cyto-histochemistry are interconnected fields that hold great promise for improving human health. Ongoing research and advancements in these areas are likely to lead to innovative treatments and therapies for a range of diseases and conditions.